Anticancer Activity of Trigona sp. Honey against Breast Cancer, Colon Cancer, and Lung Cancer - Bustomi - Bustomi; Akhmad Endang Zainal - Hasan; Khaswar - Syamsu (Universitas Lambung Mangkurat, 2023)
Since ancient times, honey has been utilized as a medication, while Trigona sp. honey is a special kind of honey. Breast, colon, and lung cancers are very malignant types of cancer and need to be treated with caution This investigation intended to establish the in vitro toxicity activity of eight Trigona sp. honey opposed to breast cancer (MCF-7), colon cancer (WiDr), and lung cancer (A549). Cytotoxicity using the MTT test technique (3,4,5-dimethylthiazole-2-yl)-2,5-diphenyltetrazolium bromide). The honey used is Trigona sp. honey with Indonesian standards and the concentration of honey tested is 5.5%. The results obtained were that honey Banten 1 dan 2, Bogor, Bangka Belitung, Batu Ampar, Sumedang, Garut, and Klaten inhibited MCF-7 cancer cells by 89.46, 84.56, 77.96, 86.39, 84.58, 85.26, 88.24, 84.40; honey Banten 1 dan 2, Bogor, Bangka Belitung, Batu Ampar, Sumedang, Garut, and Klaten inhibited WiDr cancer cells by 83.22, 76.74, 68.85, 75.51, 78.53, 81.43, 81.96, 78.33; honey Banten 1 dan 2, Bogor, Bangka Belitung, Batu Ampar, Sumedang, Garut, and Klaten inhibited cancer cells A549 by 52.16, 0, 63.21, 85.92, 82.60, 84.68, 69.63, 56.38. It was found that all types of honey could inhibit cells except honey from Banten 2. The highest percentages of inhibition against MCF-7, A549, and WiDr cells were 89.46, 85.92, and 83.22 from honey Banten 1, Bangka Belitung, and Banten 1.